Enhanced Eye Velocity in Head Impulse Testing—A Possible Indicator of Endolymphatic Hydrops - Curthoys, Ian S.; Manzari, Leonardo; Rey-Martinez, Jorge; Dlugaiczyk, Julia; Burgess, Ann M. (Frontiers in Surgery, 2021)
On video head impulse testing (vHIT) of semicircular canal function, some patients reliably show enhanced eye velocity and so VOR gains greater than 1.0. Modelling and imaging indicate this could be due to endolymphatic hydrops. Oral glycerol reduces membranous labyrinth volume and reduces cochlear symptoms of hydrops, so we tested whether oral glycerol reduced the enhanced vHIT eye velocity. Study Design. Prospective clinical study and retrospective analysis of patient data. Methods. Patients with enhanced eye velocity during horizontal vHIT were enrolled (n = 9, 17 ears) and given orally 86 % glycerol, 1.5 ml/kg of body weight, dissolved 1:1 in physiological saline. Horizontal vHIT testing was performed before glycerol intake (time 0), then at intervals of 1, 2 and 3 hours after the oral glycerol intake. Control patients with enhanced eye velocity (n = 4, 6 ears) received water and were tested at the same intervals. To provide an objective index of enhanced eye velocity we used a measure of VOR gain which captures the enhanced eye velocity which is so clear on inspecting the eye velocity records. We call this measure the initial VOR gain and it is defined as: (the ratio of peak eye velocity to the value of head velocity at the time of peak eye velocity). The responses of other patients who showed enhanced eye velocity were analyzed to try to identify how the enhancement occurred. Results. We found that oral glycerol caused, on average, a significant reduction in the enhanced eye velocity response, whereas water caused no systematic change. The enhanced eye velocity during the head impulses is due in some patients, to a compensatory saccade-like response during the increasing head velocity. Conclusion. The significant reduction in enhanced eye velocity during head impulse testing following oral glycerol is consistent with the hypothesis that the enhanced eye velocity in vHIT may be caused by endolymphatic hydrops.